Microbiology : PreTest self-assessment and review - kettering, fletecer
The perfect way for students to assess their knowledge of microbiology for the USMLE Step 1 and course exams! Microbiology PreTest Self-Assessment and Review, 14e provides students with 500 board-style questions, answers, and concise but comprehensive explanations for correct and incorrect answer options. To ensure that questions are representative of the style and difficulty level of the exams, each PreTest book is reviewed by students who either recently passed their shelf/course exam and/or the USMLE Step 1. vignette-style questions References with every answer faciliate further research High-Yield section distills key facts--Provided by publisher.
Machine generated contents note: IntroductionAcknowledgmentsHigh Yield FactsPhysiology and Molecular MicrobiologyVirologyBacteriologyRickettsiae, Chlamydiae, and MycoplasmsMycologyParasitologyImmunologyBibliographyIndex.
Preceded by Microbiology / [edited by] James D. Kettering. 12th ed. c2007.
Includes bibliographical references and index.
Keywords: Microbiological Phenomena